Penerapan Virgin Coconut Oil terhadap Pruritus pada Pasien Gagal Ginjal Kronis - Hariyanto, Cechilya Anindhita; Nasichah, Siti Nur Alfiyatin; Ailani, Choirida; Maliya, Arina (Journal of Telenursing (JOTING), 2025)
This study aims to evaluate the effectiveness of Virgin Coconut Oil (VCO) in relieving pruritus in Chronic Kidney Disease (CKD) patients undergoing hemodialysis. The research method used is a literature review of various studies discussing VCO as a complementary therapy. The study results showed that VCO contains bioactive compounds such as lauric acid and vitamin E, which have moisturizing, anti-inflammatory, and antimicrobial properties. VCO can increase skin hydration and elasticity and help prevent skin infections that can worsen pruritus. In addition, a holistic approach that includes physical, psychological, and patient education aspects is also needed to increase the effectiveness of therapy. In conclusion, VCO has the potential to be an effective additional therapy in reducing pruritus in CKD patients undergoing hemodialysis and can be part of a more comprehensive care strategy for health workers to improve the quality of life of patients.   Keywords: Hemodialysis, CKD, Pruritus, VCO